ANALISIS POLA CURAH HUJAN DI PAPUA BARAT DAYA: Bahasa Indonesia - Melinda, Shelin; Pancariniwati, Sri; Maulana, Wahyu Taqwa; Wibowo, Krisnadi Pandu (Casuarina: Jurnal Teknik Lingkungan, 2025)
The province of Southwest Papua is characterized by its mountainous terrain, which influences the region's precipitation patterns. The typical rainfall distribution in this area takes on an "A" shape, exhibiting a peak of highest rainfall in the middle of the year. This pattern is observed in regions shaped by local features such as topography and wind systems, with significant rainfall typically occurring in June and July. To enhance the accuracy of climate forecasting, Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG) has revised its climatology data, updating the Normal Rainfall figures from the period 1981-2010 to those from 1991-2020. This updated framework serves as a reference for identifying rainfall types across Indonesian territories, particularly in eastern Indonesia and Southwest Papua. Analysis of rainfall data collected from various monitoring stations in the Southwest Papua region for the years 2020 to 2024 reveals the existence of two distinct rainfall patterns: Local type 1 observed at the Majener, Malagusa, Klasmelek, DEO Sorong Meteorological Station and Sorong Geophysics Station, and Local type 2 noted at the Walal, Klamalu, Mariyai, and Waisai rain posts. The most intense rainfall peaks typically occur in July and August, ranging from 300 - 600 mm per month, whereas the lowest precipitation levels are generally recorded in February, with values between 0 - 100 mm per month.